Flecainide intoxication in pediatric patients with supraventricular tachycardia - Guiem Vaquer; Laura Marfil; Josep Ortega; Anna Sabate-Rotes; Ferran Gran-Ipina; Ferran Roses-Noguer (Wolters Kluwer Medknow Publications, 2020)
Flecainide is a class IC antiarrhythmic indicated for ventricular and supraventricular arrhythmias in pediatric patients without structural heart disease. Flecainide has a narrow therapeutic window and proarrhythmic effect even in therapeutic doses and could lead to a life-threatening intoxication. Dosage errors, accidental intakes, and drug or food interactions, especially with dairy products, can be the cause of the intoxication. We report three consecutive cases of flecainide intoxication in children with supraventricular tachycardia (SVT) in our hospital from 2017 to 2019. Two cases had complete and spontaneous normalization of electrocardiogram (ECG) after flecainide removal. However, admission to the intensive care was required due to a sustained ventricular tachycardia in one case. Flecainide intoxication can be a life-threatening complication in patients with SVT. We believe all children should have close monitoring with serial ECG and plasma levels of flecainide during the 48-72 h after initiation of treatment, and consider hospitalization for patients <1 year of age.